The Diversity and Utilization of Fragrance Flowering Plants in Lampaya Valley, Lampaya, Muang, Yala. - Bahakheeree, Muhammadtajudin; Wutiwon, Vakin; Ayeakachi, Patimoh; Tohmoh, Subaidee; Manae, Nasree (YRU Journal of Science and Technology, 2021)
The Conservation of Fragrance Flowering Plants is necessary in study of Diversity and Utilization of Fragrance Flowering Plants in Lampaya Valley, Lampaya Sub-Distritct, Muang Yala Distritct, Yala Province was conducted from November 2018 to September 2019. by community participation and survey species of plants research. The results was found that Fragrant flowers of 13 families, 45 genera, 59 species, with family Annonaceae, the most common were 13 genera, 20 species, Desmos cochinchinensis Lour., Goniothalamus tapis Miq., Followed by family Orchidaceae, found 13 genera. 16 species, Aerides odorata Lour., Rhynchostylis retusa (L.) Blume, family Apocynaceae, found 3 genera and 3 species, Alstonia scholaris (L.) R. Br., Strophanthus gratus (Wall. & Hook.) Bail., Etc. and family Rubiaceae, found 3 genera and 3 species, Morinda elliptica Ridl., Pavetta indica L., The study of conservation was found that fragrant flowers should be propagated to reduce access to natural sources and to be used more in food, herbs, culture, landscape, and distribution to increase revenue